Knowledge and risk behaviors related to HIV/AIDS, and their association with information resource among men who have sex with men in Heilongjiang province, China - Liu, Shengyuan; Wang, Kaili; Yao, Songpo; Guo, Xiaotong; Liu, Yancheng; Wang, Binyou (BMC public health, 2010)
In Heilongjiang province, the HIV prevalence in men who have sex with men (MSM) is generally lower than other part of China. However, the official perception for their risk of HIV/AIDS infection has been increasing in the province over the years. Moreover, little information on HIV/AIDS was provided to the communities so that we have disadvantage of controlling HIV/AIDS epidemic in the region. The purpose of this study is to investigate the prevalence of HIV among MSM in Heilongjiang province, to assess their knowledge levels and risk behaviors related to HIV/AIDS, and to explore their associations with information resources. A cross-sectional study using a standardized questionnaire and blood test was administered in 2008 by local interviewers to a sample (1353) of MSM in four cities in Heilongjiang province. Among 1353 MSM, 2.3% were identified with HIV infection. About 48.7% of the subjects had multiple male sexual partners and only 37.3% of the subjects had consistent condom use (use every time) in the past 6 months. Most had a fair level of knowledge on HIV/AIDS, with the highest mean knowledge score among the MSM from Jiamusi, those with income 2000-3000 RMB/month, those searching sexual partners via internet and those performed HIV testing over 1 year ago). However, some myths regarding viral transmission (e.g., via mosquito bites or sharing kitchen utensils) also existed. Resources of information from which knowledge and risk behaviors related to HIV/AIDS was most available were television (58.6%) among MSM, followed by sexual partner (51.6%), publicity material (51.0%) and internet (48.7%). Significantly statistical differences of mean knowledge score were revealed in favor of book (P = 0.0002), medical staff (P = 0.0007), publicity material (P = 0.005) and sexual partner (P = 0.02). Press (P = 0.04) and book (P = 0.0003) were contributory to the most frequent condom use (condom use every time), while medical staff (P = 0.005) and publicity material (P = 0.04) is associated with moderate rate of condom use (condom use often). Although the prevalence of HIV infection is low among MSM in Heilongjiang province, the situation that the risk behaviors were frequent in the population is alarming. The study suggests that some strategies like condom use and education intervention are practical approaches and need to be strengthened.